Cefuroxime derived copper nanoparticles and their application as a colorimetric sensor for trace level detection of picric acid. Issue 86 (1st September 2016) - Hussain, Masood; Nafady, Ayman; Sirajuddin,; Hussain Sherazi, Syed Tufail; Shah, Muhammad Raza; Alsalme, Ali; Kalhoro, Muhammad Siddique; Mahesar, Sarfaraz Ahmed; Siddiqui, Samia
Abstract : Picric acid is used as explosive material in destructive weapons and nuclear technology. Due to higher solubility in water it can create health issues and its monitoring is crucial for safer environment and health. Abstract : Picric acid (PA) is an explosive material often used in explosive tools, destructive weapons and nuclear technology. In this work we demonstrate a simple, novel and efficient wet chemical protocol for fabricating copper nanoparticles using cefuroxime drug as a protecting agent. Cefuroxime functionalized copper nanoparticles (Cefu-CuNPs) were initially confirmed and characterized via UV-Visible (UV-Vis) spectroscopy. Surface interaction between cefuroxime and copper nanoparticles was investigated by Fourier transform infrared (FTIR) spectroscopy while their shapes and size were observed via Atomic Force Microscopy (AFM) where an average size of 30.3 ± 2 nm was recorded. As-synthesized Cefu-CuNPs were used as a colorimetric sensor for detection of picric acid. Cefu-CuNPs demonstrated highly sensitive and selective colorimetric detection of picric acid in the linear range of 1.0–20 μM based on increase in intensity with an R 2 value of 0.995 determined by UV-Vis spectroscopy measurements. The resulting sensor is highly economical, simple compared to other sensors and sensitive to detect picric acid with a detection limit as low as 38 nM. The sensor can be successfully employed for picric acid detection in real water samples.